Diels–Alder reactions in confined spaces: the influence of catalyst structure and the nature of active sites for the retro-Diels–Alder reaction - Cantín, Ángel; Gomez, M. Victoria; de la Hoz, Antonio (Beilstein Journal of Organic Chemistry, 2016)
Diels–Alder cycloaddition between cyclopentadiene and p-benzoquinone has been studied in the confined space of a pure silica zeolite Beta and the impact on reaction rate due to the concentration effect within the pore and diffusion limitations are discussed. Introduction of Lewis or Brønsted acid sites on the walls of the zeolite strongly increases the reaction rate. However, contrary to what occurs with mesoporous molecular sieves (MCM-41), Beta zeolite does not catalyse the retro-Diels–Alder reaction, resulting in a highly selective catalyst for the cycloaddition reaction.
Keywords: catalysis; Diels–Alder; retro-Diels–Alder; zeolites

(untitled) - Yilmaz, Ö.; Kus, N. S.; Tunç, T.; Sahin, E. (J. Mol. Struct., 2015)

(untitled) - Yamabe, S.; Dai, T.; Minato, T. (J. Am. Chem. Soc., 1995)

(untitled) - Cativiela, C.; Fraile, J. M.; García, J. I.; Mayoral, J. A.; Pires, E.; Royo, A. J.; Figueras, F.; de Ménorval, L. C. (Tetrahedron, 1993)

(untitled) - Song, S.; Wu, G.; Dai, W.; Guan, N.; Li, L. (J. Mol. Catal. A, 2016)

(untitled) - Cativiela, C.; Fraile, J. M.; García, J. I.; Mayoral, J. A.; Figueras, F.; de Menorval, L. C.; Alonso, P. J. (J. Catal., 1992)

(untitled) - Figueras, F.; Cativiela, C.; Fraile, J. M.; García, J. I.; Mayoral, J. A.; de Ménorval, L. C.; Pires, E. (Stud. Surf. Sci. Catal., 1994)

(untitled) - Eckert, C. A.; Grieger, R. A. (J. Am. Chem. Soc., 1970)

(untitled) - Mimoto, A.; Nakano, K.; Ichikawa, Y.; Kotsuki, H. (Heterocycles, 2010)

(untitled) - Rideout, D. C.; Breslow, R. (J. Am. Chem. Soc., 1980)

(untitled) - Wijnen, J. W.; Engberts, J. B. F. N. (J. Org. Chem., 1997)

(untitled) - Moliner, M. (Dalton Trans., 2014)

(untitled) - Climent, M. J.; Corma, A.; Iborra, S. (Green Chem., 2014)

(untitled) - Anastas, P. T.; Kirchhoff, M. M. (Acc. Chem. Res., 2002)

Handbook of Green Chemistry; Green Catalysis, Heterogeneous Catalysis - Brown, S. H. (Zeolites in Catalysis, 2009)

(untitled) - Corma, A. (J. Catal., 2003)

(untitled) - Corma, A.; García, H. (Chem. Rev., 2003)

(untitled) - Koehle, M.; Lobo, R. F. (Catal. Sci. Technol., 2016)

(untitled) - Kang, J.; Rebeck, J., Jr (Nature, 1997)

(untitled) - Orazov, M.; Davis, M. E. (Chem. Sci., 2016)

(untitled) - Chang, C.-C.; Cho, H. J.; Yu, J.; Gorte, R. J.; Gulbinski, J.; Dauenhauer, P.; Fan, W. (Green Chem., 2016)

(untitled) - Zendehdel, M.; Zamani, F.; Khanmohamadi, H. (Microporous Mesoporous Mater., 2016)

(untitled) - Onaka, M.; Yamasaki, R. (Chem. Lett., 1998)

(untitled) - Kugita, T.; Ezawa, M.; Owada, T.; Tomita, Y.; Namba, S.; Hashimoto, N.; Osaka, M. (Microporous Mesoporous Mater., 2001)

(untitled) - Mahmoud, E.; Yu, J.; Gorte, R. J.; Lobo, R. F. (ACS Catal., 2015)

(untitled) - Green, S. K.; Patet, R. E.; Nikbin, N.; Williams, C. L.; Chang, C.-C.; Yu, J. Y.; Gorte, R. J.; Caratzoulas, S.; Fan, W.; Vlachos, D. G.; Dauenhauer, P. J. (Appl. Catal., B, 2016)

(untitled) - Corma, A. (Catal. Rev.: Sci. Eng., 2004)

(untitled) - Pacheco, J. J.; Labinger, J. A.; Sessions, A. L.; Davis, M. E. (ACS Catal., 2015)

(untitled) - Pacheco, J. J.; Davis, M. E. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Mashayekhi, G.; Ghandi, M.; Farzaneh, F.; Shahidzadeh, M.; Najafi, H. M. (J. Mol. Catal. A: Chem., 2007)

(untitled) - Gómez, M. V.; Cantín, A.; Corma, A.; de la Hoz, A. (J. Mol. Catal. A: Chem., 2005)

(untitled) - Blasco, T.; Corma, A.; Esteve, P.; Guil, J. M.; Martinez, A.; Perdigon-Melon, J. A.; Valencia, S. (J. Phys. Chem. B, 1998)

(untitled) - Corma, A.; Nemeth, L. T.; Renz, M.; Valencia, S. (Nature, 2001)

(untitled) - Camblor, M. A.; Corma, A.; Valencia, S. (J. Mater. Chem., 1998)

(untitled) - Dutta, S.; De, S.; Saha, B.; Alam, M. I. (Catal. Sci. Technol., 2012)

(untitled) - Corma, A.; Díaz-Cabañas, M. J.; Jordá, J. L.; Martínez, C.; Moliner, M. (Nature, 2006)

(untitled) - Sun, J.; Bonneau, C.; Cantín, Á.; Corma, A.; Díaz-Cabañas, M. J.; Moliner, M.; Zhang, D.; Li, M.; Zou, X. (Nature, 2009)

Proceedings of the 13th International Zeolite Conference, Vol. 153 - Elomari, S.; Zones, S. I. (Zeolites and Mesoporous Materials at the Dawn of the 21st Century, Montpellier, France, 2001)

U.S. Patent - Chen, C. Y.; Zones, S. I. (Preparation of aluminum-, gallium-, and iron-exchanged borosilicate zeolites and their use as petroleum refining catalysts, 2003)

(untitled) - Burton, A.; Elomari, S.; Chen, C.-Y.; Medrud, R. C.; Chan, I. Y.; Bull, L. M.; Kibby, C.; Harris, T. V.; Zones, S. I.; Vittoratos, E. S. (Chem. – Eur. J., 2003)

Recent Advances in the Science and Technology of Zeolites and Related Materials, Proceedings of the 14th International Zeolite Conference, Vol. 154A, pp 126–132. - Burton, A.; Elomari, S.; Chen, C. Y.; Harris, T. V.; Vittoratos, E. S. (Cape Town, South Africa, 2004)

U.S. Patent - Elomari, S. (Zeolite SSZ-53 prepared by using templating agent to be catalyst, 2002)

(untitled) - Yates, P.; Switlak, K. (Can. J. Chem., 1990)